Therapy for Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 1988)
A 12 year-old male with Tourette Syndrome whose symptoms improved with gum chewing is reported from the Division of Pediatric Neurology, Hahnemann University, Philadelphia, PA.